Keterampilan Literasi Siswa Ditinjau dari Pengetahuan Metakognisi dalam Menyelesaikan Soal Asesmen Kompetensi Minimum di Sekolah Dasar - Arizka, Galuh Fista; Purnamasari, Iin; Patonah, Siti (Pena Edukasia, 2022)
The background that drives this research is that the literacy skills of students at SDN 01 Wonokromo are good but there are still some that are lacking, especially in solving the existing Minimum Competency Assessment questions. The purpose of this study was to analyze students' literacy skills in solving Minimum Competency Assessment questions at SDN 01 Wonokromo. This type of research uses a qualitative description approach using the methods of observation, interviews, questionnaires, and documentation. The results showed that student's literacy skills in solving AKM questions were well known from observations to the distribution of questionnaires carried out in class V. Knowledge of AKM and student literacy was carried out well and went smoothly with an average score of 74%, supporting facilities and infrastructure the activities owned are very good with a score of 81%. The involvement of teachers, principals, and education personnel is good with an average score of 73%. All school communities participate in helping students in the AKM process and overcoming various obstacles that students experience with an average score of 63%. Based on the results of the research, the suggestions concluded that students' literacy skills in solving Minimum Competency Assessment questions can be improved again so that students will understand more about the questions and can get more satisfactory grades.